Quotas for women in politics : gender and candidate selection reform worldwide - Krook, Mona Lena (Oxford University Press, 2009)
In recent years, political parties and national legislatures in more than one hundred countries have adopted quotas for the selection of female candidates to political office. Despite the rapid international diffusion of these measures, most research has focused on single countries - or, at most, the presence of quotas within one world region. Consequently, explanations for the adoption and impact of gender quotas derived from one study often contradict with findings from other cases. Quotas for Women in Politics is the first book to address quotas as a global phenomenon to explain their spread and impact in diverse contexts around the world. It is organized around two sets of questions. First, why are quotas adopted? Which actors are involved in quota campaigns, and why do they support or oppose quota measures? Second, what effects do quotas have on existing patterns of political representation? Are these provisions sufficient for bringing more women into politics? Or, does their impact depend on other features of the broader political context? Synthesizing literature on quota policies, this book develops a framework for analyzing the spread of quota provisions and the reasons for variations in their effects. It then applies this framework to examine and compare campaigns for reserved seats in Pakistan and India, party quotas in Sweden and the United Kingdom, and legislative quotas in Argentina and France.